Health needs and interests of grade I, II, and III pupils of the Northern Luzon Teachers College Laboratory School and their implications for health instruction - Garcia, Brigida D. 1922- (s.n.], 1969)
The aim of the study is to identify the health needs and interests of Grades I, II and III pupils of the Laboratory School using the normative survey method. Results of the study may be used to provide meaningful health experiences for boys and girls. Likewise, the discovered needs and interests of pupils may be used as one of the bases in selecting what to teach and lastly, the study can help indicate the problem to be studied and the concepts and activities that should be developed at each of the three grade levels--Grades I, II and III.